AMPA receptors as a molecular target in epilepsy therapy. (11th March 2013) - Rogawski, M. A.
Abstract : Epileptic seizures occur as a result of episodic abnormal synchronous discharges in cerebral neuronal networks. Although a variety of non‐conventional mechanisms may play a role in epileptic synchronization, cascading excitation within networks of synaptically connected excitatory glutamatergic neurons is a classical mechanism. As is the case throughout the central nervous system, fast synaptic excitation within and between brain regions relevant to epilepsy is mediated predominantly by AMPA receptors. By inhibiting glutamate‐mediated excitation, AMPA receptor antagonists markedly reduce or abolish epileptiform activity in in vitro preparations and confer seizure protection in a broad range of animal seizure models. NMDA receptors may also contribute to epileptiform activity, but NMDA receptor blockade is not sufficient to eliminate epileptiform discharges. AMPA receptors move into and out of the synapse in a dynamic fashion in forms of synaptic plasticity, underlying learning and memory. Often, the trigger for these dynamic movements is the activation of NMDA receptors. While NMDA receptor antagonists inhibit these forms of synaptic plasticity, AMPA receptor antagonists do not impair synaptic plasticity and do not inhibit memory formation or retrieval. The demonstrated clinical efficacy of perampanel, a high‐potency, orally active non‐competitive AMPA receptor antagonist, supports the concept that AMPA receptors are critical to epileptic synchronization and the generation and spread of epileptic discharges in human epilepsy.